2021
DOI: 10.2147/idr.s298530
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and Clinical Outcomes of Carbapenem-Resistant Klebsiella pneumoniae Nosocomial Infections: A Retrospective Study in a Tertiary Hospital in Beijing, China

Abstract: Purpose Carbapenem-resistant Klebsiella pneumoniae (CRKP) infections have been increasingly reported worldwide. We aimed to identify the risk factors for nosocomial CRKP infections and assess the clinical outcomes. Patients and Methods We conducted a case-control study with data collected from January 2016 to December 2018 in China. Controls were selected at a ratio of 1:1 from patients with nosocomial carbapenem-susceptible Kleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
(24 reference statements)
2
12
0
1
Order By: Relevance
“…Previous studies have demonstrated CRKP patients had shorter survival time than CSKP patients. 14 , 15 Similar to these studies, we also found CRKP was an important risk factor for 30-day mortality rates. The main reason is due to limited antibiotic options for CRKP, resulting in poor prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have demonstrated CRKP patients had shorter survival time than CSKP patients. 14 , 15 Similar to these studies, we also found CRKP was an important risk factor for 30-day mortality rates. The main reason is due to limited antibiotic options for CRKP, resulting in poor prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…Clinical features such as requiring MV support, high SOFA score, having septic shock at the onset, and having coinfection with other bacteria were strongly associated with inhospital mortality. Meanwhile, appropriate definitive antimicrobial therapy did not protect against mortality, similar to findings from earlier studies (de Maio Carrilho et al, 2016;Zhang et al, 2021). CRE infection also increased hospital costs, mainly due to the requirement for more intensive medical care and prolonged hospitalization.…”
Section: Discussionsupporting
confidence: 78%
“…Our CREinfected patients had high APACHE II scores, critical illnesses requiring MV support (62.86%), and required placement of CVC (49.00%) before the onset. Likewise, two other studies concluded that patients infected by carbapenemresistant strains were more likely to have respiratory compromise and unstable hemodynamics requiring MV support and CVC placement than those infected by carbapenem-susceptible strains (Wang et al, 2016;Zhang et al, 2021). The onset of CRE infection varied from a few days to several weeks following hospital admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Moreover, CRE infections have resulted in substantial morbidity and mortality among hospitalized patients worldwide. [26][27][28] In the era of the increasing incidence of CRE infections, the clinical impact of the coexistence of CRE infections among hospitalized patients with CDI was not clear. The objective of this study is to investigate the risk factors and clinical impact of CRE infections among hospitalized patients with CDI.…”
Section: Introductionmentioning
confidence: 99%